1993
DOI: 10.1111/j.1365-2362.1993.tb00737.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of intestinal absorption of cholesterol with different plant sterols in man*

Abstract: Intestinal absorption of cholesterol, campesterol, campestanol, stigmasterol and sitosterol were measured in 10 healthy subjects by an intestinal perfusion technique over a 50 cm segment of the upper jejunum using sitostanol as non-absorbable marker. Cholesterol absorption was highest and averaged 33%., whereas the absorption rate of sitosterol averaged 4.2% and of stigmasterol 4.8%. Higher absorption rates were found for campesterol (9.6%). Campestanol, the 5 alpha saturated derivative of campesterol, showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
222
0
5

Year Published

2000
2000
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 367 publications
(236 citation statements)
references
References 29 publications
9
222
0
5
Order By: Relevance
“…A similar, although weaker correlation has been reported by Miettinen, who found a coef®-cient of correlation of 7 0.25 between dietary plant sterols, determined as faecal plant sterols, and fractional cholesterol absorption in 63 middle-aged men on self-selected diets (Miettinen & Kesaniemi, 1989). This is also in agreement with human perfusion studies where there was a similar negative correlation between fractional cholesterol absorption and the ratio of sitosterol to cholesterol presented in the perfusion tube (Heinemann et al, 1993). There was also a negative correlation between cholesterol absorption and dietary ®bre excretion, although somewhat weaker than for plant sterol excretion (r Pearson 7 0.64).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…A similar, although weaker correlation has been reported by Miettinen, who found a coef®-cient of correlation of 7 0.25 between dietary plant sterols, determined as faecal plant sterols, and fractional cholesterol absorption in 63 middle-aged men on self-selected diets (Miettinen & Kesaniemi, 1989). This is also in agreement with human perfusion studies where there was a similar negative correlation between fractional cholesterol absorption and the ratio of sitosterol to cholesterol presented in the perfusion tube (Heinemann et al, 1993). There was also a negative correlation between cholesterol absorption and dietary ®bre excretion, although somewhat weaker than for plant sterol excretion (r Pearson 7 0.64).…”
Section: Discussionsupporting
confidence: 85%
“…Plant sterol excretion will re¯ect dietary intake, as the absorption of b-sitosterol, the major component of plant sterols, is very poor (Salen et al, 1970;Heinemann et al, 1993). A similar, although weaker correlation has been reported by Miettinen, who found a coef®-cient of correlation of 7 0.25 between dietary plant sterols, determined as faecal plant sterols, and fractional cholesterol absorption in 63 middle-aged men on self-selected diets (Miettinen & Kesaniemi, 1989).…”
Section: Discussionmentioning
confidence: 58%
“…PS have been suggested to reduce serum cholesterol concentrations by competitively blocking cholesterol absorption from the intestinal lumen (Heinemann et al, 1986(Heinemann et al, , 1993, displacing cholesterol from bile salt micelles (Child & Kukis, 1986), increasing bile salt excretion (Salen et al, 1970), or hindering the cholesterol esteri®cation rate in the intestinal mucosa (Child & Kukis, 1983;Ikeda & Sugano, 1983). Ikeda et al also showed that the only site of action was during binding of sterols to micelles (Ikeda et al, 1988).…”
Section: Solubilization Of Phytosterols S Meguro Et Almentioning
confidence: 99%
“…Plant sterols are absorbed from 5% (sitosterol) to 15% (campesterol) (Heinemann et al, 1993;Salen et al, 1970). Furthermore, plant sterols and stanols may interfere with the absorption of carotenoids, as indicated by reduced serum carotenoid concentrations (Gylling et al, 1999b;Hallikainen et al, , 2000Hendriks et al, 1999;Weststrate & Meijer, 1998).…”
Section: Introductionmentioning
confidence: 99%